Concentration Transitions on the Crystalline Lattices - N.A. Gorenko; K.V. Nefedev (Журнал нано- та електронної фізики)
Results of numerical modeling of dilute 2D and 3D crystalline lattices are presented. The percolation thresholds for face-centered cubic (fcc), body-centered cubic (bcc) and the simple cubic (sc) lattices for the first, second and third coordination spheres are obtained by means of Monte Carlo (MC) method. It is shown, that the mean value of the percolation cluster density has a minimum value at the percolation threshold.